PENGARUH FAKTOR INTERNAL, FAKTOR EKSTERNAL DAN STRATEGI PEMBERIAN KREDIT TERHADAP NON PERFORMING LOAN PADA BANK PEMBANGUNAN DAERAH BALI - Dwi Aryanthi, I Gusti Ayu Wika; Andayani W, Rai Dwi (Hita Akuntansi dan Keuangan, 2022)
The purpose of this research was to determine the effect of the application of effec internal Factor, external factor and strategy of loan on non performing loan at Bank Pembangunan Daerah Bali. This research was conducted at Bank Pembangunan Daerah Bali. The number of samples used is 98 people, with porpusive random sampling. The data collection is has been finished questionnaires. The analytical technique used is multiple linear regression. The results of hypothesis testing indicate that internal factor have a positive effect on non performing loan at Bank Pembangunan Daerah Bali. External factor have a positive effect on non performing loan at Bank Pembangunan Daerah Bali. There is positive impact of the lending strategy on non-performing loans at the BPD Bali.